(untitled) (World Economics and Finance Bulletin, 2021)
The article provides information on the history of tales about youngest son and their place in English literature. There are also points of various scholars and their researches on the history of the fairy tales, its development and factors that served as the cause of their origin in the work. In addition, the sample named “The King of England and his Three Sons” by J.Jacob was analyzed using examples.